Scheme of thermal compression of hydrogen (TCH) using MmNi4.25Al0.75 recovered with ethyl alcohol and handled under non protective atmospheres - Obregon, Sergio Alejandro (2014)
A MmNi4.25Al0.75 intermetallic was obtained by low energy mechanical alloying and low temperature heating at 600 °C for 24 h under Ar. The intermetallic was recovered from milling chamber using ethyl alcohol, dried, stored and handled under air at room conditions. Structure was characterized by XRD. A maximum stability temperature of 160 °C was obtained from non-isothermal DSC measurement under air. The kinetics of oxidation at 200 °C was analyzed. A maximum reaction degree (α = 0.1) was obtained after 2500 s of treatment. The hydrogen sorption properties of samples were studied by volumetric measurements. Hydrogen maximum mass percent capacity (mass %) was reached in less than 300 s. The thermodynamic sorption properties were measured. Values of ΔHf = −29 ± 2 kJ mol−1 and ΔSf = 197 ± 10 J mol−1 K−1 were obtained for absorption process and ΔHd = 28 ± 2 kJ mol−1 and ΔSd = 189 + 10 J mol−1 K−1 were obtained for desorption process. From these results, a one-stage of thermal compression of hydrogen is proposed with a standard compression ratio (Rc) of 5.71 in the 25–80 °C range.